2010
DOI: 10.1159/000320308
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neopterin, C-Reactive Protein and Myeloperoxidase in Patients Undergoing Cardiopulmonary Bypass

Abstract: Objective: The aim of the present study was to investigate the role of neopterin (NP), C-reactive protein (CRP) and myeloperoxidase (MPO) in patients undergoing coronary artery bypass grafting with or without cardiopulmonary bypass (CPB). Patients and Methods: Forty patients submitted for elective coronary artery bypass grafting were included in this prospective study. Patients were divided into two groups of 20 individuals, those who did not undergo CPB (group 1), aged 54.1 ± 13.5 years, and those who did (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…In the present study, we found no correlation between CRP and neopterin levels in elective cardiac surgery patients, although CRP levels were significantly higher in elective cardiac surgery patients than in acutely ill medical patients. A previous study, performed in patients who underwent CABG, showed that both CRP and neopterin levels increased after on-pump CABG, but the increase was significantly greater for CRP than for neopterin 34. This finding suggests a poor correlation between CRP and neopterin after on-pump CABG, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we found no correlation between CRP and neopterin levels in elective cardiac surgery patients, although CRP levels were significantly higher in elective cardiac surgery patients than in acutely ill medical patients. A previous study, performed in patients who underwent CABG, showed that both CRP and neopterin levels increased after on-pump CABG, but the increase was significantly greater for CRP than for neopterin 34. This finding suggests a poor correlation between CRP and neopterin after on-pump CABG, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with previous animal and human studies in which penehyclidine hydrochloride or dexmedetomidine had an effect on in ammatory factors such as IL-6 and TNF-α [18,38] . At 6 h after CPB, the concentration of CRP in the four groups began to increase, which was more obvious at 24 h after CPB than preoperatively, which was similar to the typical change trend of CRP after cardiopulmonary bypass [39] . Previous studies found that penehyclidine hydrochloride reduced high-sensitivity CRP in patients with acute ischemia/reperfusion injury after cardiopulmonary resuscitation [40] .…”
Section: Discussionsupporting
confidence: 66%
“…This could be related to the inflammatory response mediated by advancing age through a variety of molecular mechanisms such as the mitochondrial adaptor protein p66 (Shc) and the family of deacetylase enzymes, the sirtuins [16] . In addition to the normal ageing process, cardiac surgery itself induces a systemic inflammatory response [17] . A previous study reported higher serum resistin levels both in the pre-and postoperative phases along with other proinflammatory markers (IL-6, IL-10, and CRP) [18] .…”
Section: Discussionmentioning
confidence: 99%